The psychoanalysis of organizations : a psychoanalytic approach to behaviour in groups and organizations - De Board, Robert (New York ; London : Routledge, 2014)
"One of the most pressing needs of modern society is to understand and construct organizations that are not only effective in terms of carrying out work but that also allow and encourage people to develop their full human potential. Psychoanalytic theory describes those primary processes that lie at the heart of human activity and provides new insights for understanding group and organizational behaviour. With a new introduction written by Vega Roberts, this Classic Edition of The Psychoanalysis of Organizations presents the theories of Sigmund Freud, Melanie Klein, Wilfred Bion, Elizabeth Lewin and Eric Menzies in plain language and shows their relevance to normal working life. First published in 1978, Robert De Board takes a wide-ranging overview of the major psychoanalytic theorists and organizational researchers, and analyses how the two groups can work together. Written in a very accessible style, it makes sophisticated psychoanalytic and management concepts comprehensible and usable for anyone"--
Includes bibliographical references and index.
Keywords: Organizational sociology; Organizational behavior; Psychoanalysis; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; PSYCHOLOGY / Movements / Psychoanalysis